2019
DOI: 10.1002/bmc.4521
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of nine major bioactive components in normal and ulcerative colitis rats after oral administration of Lizhong decoction extracts by UPLC–TQ–MS/MS

Abstract: Lizhong decoction (LZD), a classic formula, has been used to treat ulcerative colitis (UC) for thousands of years in clinical practice. However, the pharmacokinetic characteristics of its major bioactive components in rats under different physiological and pathological states are not clear. Thus, in this study, a rapid and sensitive analytical method, ultra‐performance liquid chromatography coupled with mass spectrometry (UPLC–MS/MS) method, was developed and applied to simultaneously determine glycyrrhizic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In the NAFLD rats, the clearance rate of glycyrrhizic acid, glycyrrhetinic acid, dehydrotumulosic acid, isoliquiritin, liquiritin, atractylenolide III, and cinnamic acid was significantly higher than that of the normal group. There was also a bimodal phenomenon between glycyrrhetinic acid and isoliquiritin ( Xu et al, 2018 ; Shen et al, 2019 ), which might have been caused by gastric emptying separation, enterohepatic circulation, and reabsorption ( Deng et al, 2008 ; Zhu et al, 2010 ). Further research should be carried out to determine the specific mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…In the NAFLD rats, the clearance rate of glycyrrhizic acid, glycyrrhetinic acid, dehydrotumulosic acid, isoliquiritin, liquiritin, atractylenolide III, and cinnamic acid was significantly higher than that of the normal group. There was also a bimodal phenomenon between glycyrrhetinic acid and isoliquiritin ( Xu et al, 2018 ; Shen et al, 2019 ), which might have been caused by gastric emptying separation, enterohepatic circulation, and reabsorption ( Deng et al, 2008 ; Zhu et al, 2010 ). Further research should be carried out to determine the specific mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…LZD consists of four herbs such as Zingiberis Rhizoma (Ganjiang in Chinese) , Ginseng Radix et Rhizoma (Renshen in Chinese) , Atractylodis Macrocephalae Rhizoma (Baizhu in Chinese) , and Glycyrrhizae Radix et Rhizoma (Gancao in Chinese) ( Shen, Cui, Jiang, Qian, & Duan, 2019 ), which is a traditional herbal formula widely used for gastrointestinal diseases due to deficiency-cold of the spleen and stomach in China for a long history. LZD treatment [1.365, 4.095 and 12.285 g/(kg·d) for 14 d] showed a favorable regulative effect on gut microbiota diversity in UC mice induced by DSS ( Zou et al, 2020 ).…”
Section: Chinese Herbal Medicine For Treatment Of Experimental Colitismentioning
confidence: 99%
“…Rats were allowed to acclimatize to the animal facility for 7 days before experimental procedures. The UC rat model was induced by 2,4,6-trinitrobenzene sulfonic acid (TNBS)/ethanol enema according to the protocol reported previously [23,24]. Briefly, all rats were fasted for 24 h with free access to drinking water and then were anesthetized using sodium pentobarbital (50 mg/kg, ip).…”
Section: Animalsmentioning
confidence: 99%
“…Pharmacokinetics of four analytes in ulcerative colitis rat plasma A large number of studies have shown that the pharmacokinetic process of drugs might be changed in the pathological state [23,30]. Thus, it was necessary to investigate pharmacokinetic characteristics of four components in UC rat plasma after oral administration of ZR, GR, and ZG extracts.…”
Section: 42mentioning
confidence: 99%